Helping organisations excel, one breath at a time: A meditation toolkit for business leaders - MASTERS-WAAGE, Theodore Charles (Institutional Knowledge at Singapore Management University, 2021)
Interest in meditation has risen dramatically in recent years, as these practices move beyond ancient monasteries to take root in big cities as well.